Do recreational fisheries metrics vary on differently sized fishing grounds?. (2nd July 2018) - Lyach, Roman; Čech, Martin
Abstract: This study aimed to assess the relationship between basic metrics in recreational fishing and the size of the fishing ground. Data were obtained from individual angling logbooks collected by the Czech Fishing Union over 12 years on 212 fishing grounds located in the regions of Prague and Central Bohemia in the Czech Republic. Small fishing grounds had the highest catch, yield, numbers of fishing visits and numbers of angling guard controls per hectare. Medium‐sized fishing grounds had the highest catch, yield, and numbers of both fishing visits and angling guard controls per fishing ground. Anglers returned to medium‐sized fishing grounds most frequently. The percentage of anglers who caught and took home at least one fish decreased with increasing size of the fishing ground. In conclusion, basic metrics in recreational fishing are related to the size of the fishing ground, which thus plays an important role in fisheries management.